Implementing the Balanced Scorecard in Public Organization: An Experience in Communication Affairs Bureau Dire Dawa Administration, Ethiopia (Global Journal of Management and Business Research, 2020)
Abstract not found
Keywords: balance scorecard; performance measurement; evaluation